EDUKASI BAHAYA GADGET DAN FESTIVAL KEBAIKAN: WUJUD PENGABDIAN UKM PRO.ASTA UNIVERSITAS BATTUTA - Ruziq, Fahmi; Wayahdi, M. Rhifky; Nanda Ginting, Subhan Hafiz; Wahyuni, Dewi; Sridewi, Nurmala (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract: The development of digital technology brings both conveniences and challenges for children. Excessive gadget use can negatively impact children’s physical, psychological, and social well-being. The community service programme "Education on the Dangers of Gadgets and Kindness Festival" aims to provide education about the dangers of excessive gadget use while introducing various healthy and enjoyable alternative activities. The method applied was participatory and educational through counselling, educational games, traditional games, and a kindness festival. The results showed an increase in children’s awareness of the negative impacts of gadgets and their interest in engaging in beneficial non-gadget activities. This activity is expected to become a preventive effort to reduce children's dependence on gadgets in the digital era.            Keywords: children's activities; educational gadgets; kindness festival; educational games; community service.  Abstrak: Perkembangan teknologi digital membawa kemudahan sekaligus tantangan bagi anak-anak. Penggunaan gadget yang berlebihan dapat berdampak negatif terhadap kesehatan fisik, psikologis, dan sosial anak. Kegiatan pengabdian kepada masyarakat “Edukasi Bahaya Gadget dan Festival Kebaikan” bertujuan untuk memberikan edukasi tentang bahaya penggunaan gadget berlebihan sekaligus mengenalkan berbagai aktivitas alternatif yang sehat dan menyenangkan. Metode yang digunakan bersifat partisipatif dan edukatif melalui penyuluhan, permainan edukatif, permainan tradisional, dan festival kebaikan. Hasil kegiatan menunjukkan peningkatan kesadaran anak-anak tentang dampak negatif gadget serta tumbuhnya ketertarikan terhadap aktivitas non-gadget yang bermanfaat. Kegiatan ini diharapkan dapat menjadi salah satu solusi preventif dalam menekan ketergantungan anak terhadap gadget di era digital. Kata kunci: aktivitas anak; edukasi gadget; festival kebaikan; permainan edukatif; pengabdian masyarakat